Levels of Adherence to Coartem© In the Routine Treatment of Uncomplicated Malaria in Children Aged Below Five Years, in Kenya - Jared Otieno Ogolla; Samuel Omulando Ayaya; Christina Agatha Otieno (Tehran University of Medical Sciences, 2013)
Background: This study sought to determine the level of adherence to Coartem© in the routine treatment of uncomplicated malaria among children under the age of five years in Nyando district, Kenya.Methods: Seventy-three children below the age of five years with microscopically confirmed uncomplicated Plasmodium falciparum malaria and prescribed Coartem® during the normal outpatient department hours were included into the study on 27th of April to 15th of May 2009. Adherence was assessed through a semi-structured interviewer administered questionnaire; pill count and blister pack recovery. Patients were then classified into three categories of adherence. Patients who had tablets remaining in the blister pack were classified as definitely non-adherent. Those who had blister pack missing or empty and the caretaker did not report administering all the doses at the correct time and amount were considered probably non-adherent or as probably adherent when the caretaker reported administering all doses at the correct time and amount.Results: Nine (14.5%) patients were definitely non-adherent, 6 (9.7%) probably non-adherent and 47 (75.8%) probably adherent. The most significantly left tablet was the sixth doses (P = 0.029).Conclusion: Caretakers should be made much aware that non-adherence might not only be dangerous to child's health but also dramatically increase the financial cost for public-health services.